Spatio‐temporal patterns of tree growth as related to carbon isotope fractionation in European forests under changing climate. Issue 9 (7th June 2019) - Shestakova, Tatiana A.; Voltas, Jordi; Saurer, Matthias; Berninger, Frank; Esper, Jan; Andreu‐Hayles, Laia; Daux, Valérie; Helle, Gerhard; Leuenberger, Markus; Loader, Neil J.; Masson‐Delmotte, Valérie; Saracino, Antonio; et al.
Abstract: Aim: The aim was to decipher Europe‐wide spatio‐temporal patterns of forest growth dynamics and their associations with carbon isotope fractionation processes inferred from tree rings as modulated by climate warming. Location: Europe and North Africa (30‒70° N, 10° W‒35° E). Time period: 1901‒2003. Major taxa studied: Temperate and Euro‐Siberian trees. Methods: We characterize changes in the relationship between tree growth and carbon isotope fractionation over the 20th century using a European network consisting of 20 site chronologies. Using indexed tree‐ring widths (TRWi ), we assess shifts in the temporal coherence of radial growth across sites (synchrony) for five forest ecosystems (Atlantic, boreal, cold continental, Mediterranean and temperate). We also examine whether TRWi shows variable coupling with leaf‐level gas exchange, inferred from indexed carbon isotope discrimination of tree‐ring cellulose (Δ 13 Ci ). Results: We find spatial autocorrelation for TRWi and Δ 13 Ci extending over a maximum of 1, 000 km among forest stands. However, growth synchrony is not uniform across Europe, but increases along a latitudinal gradient concurrent with decreasing temperature and evapotranspiration. Latitudinal relationships between TRWi and Δ 13 Ci (changing from negative to positive southwards) point to drought impairing carbon uptake via stomatal regulation for water saving occurring at forests below 60° N in continental Europe. An increase in forest growth synchrony over the 20th century together with increasingly positive relationships between TRWi and Δ 13 Ci indicate intensifying impacts of drought on tree performance. These effects are noticeable in drought‐prone biomes (Mediterranean, temperate and cold continental). Main conclusions: At the turn of this century, convergence in growth synchrony across European forest ecosystems is coupled with coordinated warming‐induced effects of drought on leaf physiology and tree growth spreading northwards. Such a tendency towards exacerbated moisture‐sensitive growth and physiology could override positive effects of enhanced leaf intercellular CO2 concentrations, possibly resulting in Europe‐wide declines of forest carbon gain in the coming decades.